Social entrepreneurship and Economy for the Common Good: Study of their relationship through a bibliometric analysis. (August 2020) - Campos, Vanessa; Sanchis, Joan-Ramon; Ejarque, Ana
Being social entrepreneurship (SE) the closest to Economy for the Common Good (ECG) principles, our work proposes to analyze the contribution of ECG model to SE. It is also intended to establish the relationship that exists between both concepts. Therefore, our specific objectives are to (1) identify the specific contributions of ECG principles to SE as well as their overlaps, (2) perform a literature review to analyze and quantify the number of research papers on SE and ECG, and (3) identify the possible existing gap. Through a double methodology, we (1) determine the potential contributions of the ECG model to SE, we propose to analyze the Common Good (CG) matrix and (2) empirical analysis on the existing literature body on SE and ECG. SE and ECG model share a number of principles and features which may be translated into some important overlaps in relation to both research bodies. So CG matrix can help to successfully launch and manage social ventures. This fact is mainly due to the fact that there is not a sufficiently large body of literature that relates models. In future research, it would be interesting to extend the bibliographic search to other databases.